Heartsick - Cain, Chelsea (London : Pan Books, 2008)
Damaged Portland detective Archie Sheridan spent ten years tracking Gretchen Lowell, a beautiful serial killer, but in the end she was the one who caught him. Two years ago, Gretchen kidnapped Archie and tortured him for ten days, and then mysteriously decided to let him go. She turned herself in, and now Gretchen has been locked away, while Archie is in prison of another kind-- addicted to pain pills, unable to return to his old life, powerless to get those ten horrific days off his mind. He continues to visit Gretchen in prison once a week, saying that only he can get her to reveal the whereabouts of more of her victims.
Keywords: Police -- Oregon -- Portland -- Fiction; Women serial murderers -- Fiction; Women journalists -- Fiction; Portland (Or.) -- Fiction